(untitled) (Ameghiniana, 2013)
Nine species of fossil plants have been found in a new locality "Mina La Perla", located in the vicinity of Cerro Lotena in Neuquén Province. They are: Scleropteris lotenaense n. sp., Scleropteris sp., Otozamites traoorsoi n. sp. Zamites sp., Araucarites sp., Elatocladus longifolium n. sp., Brachyphyllum ramosum n. sp., B. lotenaense n. sp. and a fructification "tipo Umkomasia o Caqtonio", Three of the species (Zamites sp., Otozamites traoersoi y Brachyphyllum ramosum) have been studied with their cuticles still preserved.